Morphology of the obturator nerve, an anatomical study with emphasis on its clinical implications [version 2; peer review: 2 approved, 1 approved with reservations, 1 not approved] - Vandana Blossom; Latha V. Prabhu; Rajanigandha Vadgaonkar; Ashwin R. Rai; Mangala M. Pai; B.V. Murlimanju (F1000Research)
Background The goal of this cadaveric cross-sectional study was to analyse the branching pattern of the obturator nerve morphologically and to determine its dimensions in embalmed cadavers. Methods In this cross-sectional study, we examined 50 embalmed adult cadaveric lower limbs. Gender was not taken into consideration in the analysis; however, a side-based comparison was performed. The measurements were performed using a digital Vernier caliper. Results The branching of obturator nerve was observed at the pelvic cavity in 28 specimens (56%) and inside the obturator canal in 12 specimens (24%). The division of obturator nerve wasn’t observed in 10 specimens (20%). The length, width and thickness of the trunk of obturator nerve was 108.26 ± 9.53 mm, 2.84 ± 0.88 mm and 1.11 ± 0.35 mm. The width and thickness of the anterior and posterior divisions of obturator nerve measured 2.19 ± 0.82 mm, 0.9 ± 0.1 mm, 0.99 ± 0.6 mm and 0.71 ± 0.26 mm. The topography of branching of obturator nerve from the superior and inferior border of the obturator foramen was located at 1.48 ± 0.58 mm and 3.07 ± 1.1 mm away. The length of anterior division of the obturator nerve measured 110.88 ± 12.02 mm over the right side and 107.13 ± 7.81 mm over the left side. The width of the main trunk of obturator nerve was 2.87 ± 0.64 mm over the right side and 2.82 ± 0.64 mm over the left side. Conclusions We believe that morphometric data of the obturator nerve will be enlightening to the operating surgeon during its procedures like nerve block, transplantation, and repairs as few of them are conducted laparoscopically, the prior knowledge of morphological dimensions and branching pattern will assist the surgeons in easy access of the obturator nerve. In this context, the dimensions of the obturator nerve observed in the present study can be utilized as a morphological database for our sample population.